1998
DOI: 10.1097/00005392-199810000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Cystectomy, Microvessel Density and Prognosis in Stage T1 Transitional Cell Carcinoma of the Bladder

Abstract: Patients with T1 bladder cancer have a high risk of recurrence and progression. Tumor progression has a significant negative impact on survival. Neither grade nor early tumor recurrence predicted disease progression. Because early cystectomy did not improve patient outcome, we suggest reserving cystectomy for patients with progression or disease refractory to local therapy. Microvessel density is not a prognostic marker for T1 bladder cancer and has no value in selecting patients with T1 disease for cystectomy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
0
17
1
2
Order By: Relevance
“…There is a risk in patients not responding to the initial induction course of BCG that further efforts at salvage therapy may result in a delay in definitive treatment that may have an adverse effect on survival probability. Long-term survival rates for patients treated with radical cystectomy for progression to muscle invasive cancer are significantly lower than for patients with ≤ pT1 at cystectomy [9,10].…”
Section: Introductionmentioning
confidence: 93%
“…There is a risk in patients not responding to the initial induction course of BCG that further efforts at salvage therapy may result in a delay in definitive treatment that may have an adverse effect on survival probability. Long-term survival rates for patients treated with radical cystectomy for progression to muscle invasive cancer are significantly lower than for patients with ≤ pT1 at cystectomy [9,10].…”
Section: Introductionmentioning
confidence: 93%
“…The median follow-up of the whole cohort was 3.8 years (0. [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. One hundred and forty-three patients (83.6%) had undergone open nephroureterectomy and 28 patients laparoscopic nephroureterectomy.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Several studies of urothelial carcinomas have indicated that MVD could be an independent negative prognostic factor (13)(14)(15)(16). However, to date evidence of the prognostic role of MVD in urothelial carcinoma is contradictory (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…han utilizado 2 modos de determinar la densidad microvascular: en el primero,o "estándar", se buscan las zonas de inmunotinción "calientes" o de mayor densidad de microvasos; en el segundo método, y para evitar el problema de la disposición papilar del núcleo fibrovascular, se realiza el contaje de los microvasos inmunoreactivos localizados entre la interfase del tumor y la lámina propia, o sea en la zona de invasión y probablemente de mayor actividad angiogénica. En su serie, el cálculo de las densidades mostró valores muy diferentes según el método utilizado, siendo mayores los recuentos netos de microvasos usando el método de la interfase tumor-lámina propia; pero no encontró correlación ni con la recidiva ni con la progresión tumoral, con ninguno de los dos métodos de análisis 28 .…”
Section: Valor Pronóstico De La Densidad Microvascularunclassified
“…analizaron la capacidad predictiva de la densidad microvascular en relación a la identificación de los pacientes en estadio T1 que deberían someterse a una cistectomía temprana; sobre una serie de 54 pacientes T1 la densidad microvascular no predijo ni recidiva ni la progresión, considerando por tanto que no constituye un marcador pronóstico y no tiene validez para seleccionar a estos pacientes 28 . Sin embargo una serie más amplia y reciente, de Goddard JC y cols.…”
Section: Valor Pronóstico De La Densidad Microvascularunclassified